Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar IPA Materi Ekologi Dan Keanekaragaman Hayati Indonesia Siswa Kelas VII.5 SMP Negeri 35 Pekanbaru Tahun Ajaran 2023/2024 - Yuni Ismaeti; Ibnu Hajar (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The purpose of this study was to improve the science learning outcomes of students in class VII.5 SMPN 35 Pekanbaru in the academic year 2023/2024 by applying the guided inquiry learning model which was carried out on February 28 to April 24, 2024 in class VII.5 SMP Negeri 35 Pekanbaru in the academic year 2023/2024 which amounted to 34 students with 17 male students and 17 female students. This research is a Classroom Action Research (CAR). The parameters measured were student learning outcomes in the form of absorption and student learning completeness consisting of individual and classical completeness. Data analysis was carried out descriptively to determine the absorption of (Cognitive) and (Psychomotor) values. The absorbency of students' scores before CAR 46.76% increased in cycle I to 47.32% and in cycle II increased again to 82.91%. Classical completeness of scores before CAR 0.00% in cycle I remained with 0.00% and increased in cycle II to 97.06%. The absorption rate of students' score before CAR was 54.11%, increased in cycle I to 75.22% and increased again to 86.35%. Classical completeness of students' scores before CAR 0.00% in cycle I increased to 85.29% and again increased to 94.12. It can be concluded that the application of the guided inquiry learning model can improve the science learning outcomes of students in class VII.5 SMP Negeri 35 Pekanbaru in the academic year 2023/2024..